STUDIES ON HOUSING MANAGEMENT OF BUFFALOES UNDER RURAL AND URBAN AREAS OF INDORE DISTRICT OF M.P. - Ahirwar, R R; Nanavati , S; Nayak, N K (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The present study was carried out in order to know the prevailing managemental practices of dairy animals in rural and urban areas of Indore district of Madhya Pradesh. Data were collected from 400 farmers of Indore district. In rural areas significantly higher number (59.33%) of farmers had mud houses and mud floor, whereas in urban areas, 68% farmers had pucca house with concrete floor. Majority of the farmers were found careful about sickness of their animals and most of them adopted prophylactic vaccination of their animals. From the study it is concluded that there is significant difference between rural and urban area in most of the managemental practices of dairy farming.
Keywords: Buffalo; Housing; Rural and Urban